Perioperative fluid infusion and its influence on anastomotic leakage after rectal cancer surgery: implications for prevention strategies. (18th September 2013) - Boesen, A. K.; Maeda, Y.; Rørbæk Madsen, M.
Abstract: Aim: This study aimed to identify modifiable risk factors for anastomotic leakage during the postoperative period to recognize areas of clinical practice that could be improved. Method: Medical charts of patients who underwent elective open anterior resection for rectal cancer over a 5‐year period were reviewed retrospectively. Results: One hundred and twenty‐four patients [64 men, mean age (± SD) 68.0 ± 9.0 years] underwent an anterior resection for rectal cancer during the study period. Twenty‐two (17.7%) patients had anastomotic leakage. Patients who were given more than 8000 ml of intravenous fluid during the 72‐h perioperative period had a statistically significant increased risk of developing anastomotic leakage [odds ratio (OR) 3.20, 95% confidence interval (CI) 1.10–9.31, P = 0.049] and the risk increased further when patients were given more than 8500 ml of intravenous fluid (OR 3.86, 95% CI 1.29–11.5, P = 0.019). The incidence of anastomotic leakage was not influenced by baseline comorbidity or tumour stage. Conclusion: Perioperative intravenous fluid of more than 8000 ml was associated with increased occurrence of anastomotic leakage. Vigorous monitoring of intravenous fluid use in the perioperative period may minimize this complication.